2006
DOI: 10.1037/1528-3542.6.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Lexical characteristics of words used in emotional Stroop experiments.

Abstract: Validity of the emotional Stroop task hinges on equivalence between the emotion and the control words in terms of lexical features related to word recognition. The authors evaluated the lexical features of 1,033 words used in 32 published emotional Stroop studies. Emotion words were significantly lower in frequency of use, longer in length, and had smaller orthographic neighborhoods than words used as controls. These lexical features contribute to slower word recognition and hence are likely to contribute to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
205
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(225 citation statements)
references
References 25 publications
13
205
1
6
Order By: Relevance
“…Emotional words, such as words having a positive or negative valence like "pleasure, love, winner" versus "loser, discomfort, sickness", form a special semantic category in the sense that the underlying semantic representation can be considered to be richer relative to neutral words, because of the additional emotional and motivational polarity which will induce an automatic categorization of the words according to a positivity / negativity dimension (e.g., Bradley, 2000). Many studies outside the STM domain have shown that emotional words elicit selective responding relative to neutral words, such as in lexical decision, naming, automatic response inhibition and vigilance tasks (Algom, Chajut, & Lev, 2004;Estes & Verges, 2008;Kanske & Kotz, 2007;Kousta, Vinson, & Vigliocco, 2009;Larser, Mercer & Balota, 2006;Pratto & John, 1991). This effect of emotional words cannot be simply reduced to an enhanced word concreteness effect.…”
Section: The Impact Of Emotional Semantic Content On Stmmentioning
confidence: 99%
“…Emotional words, such as words having a positive or negative valence like "pleasure, love, winner" versus "loser, discomfort, sickness", form a special semantic category in the sense that the underlying semantic representation can be considered to be richer relative to neutral words, because of the additional emotional and motivational polarity which will induce an automatic categorization of the words according to a positivity / negativity dimension (e.g., Bradley, 2000). Many studies outside the STM domain have shown that emotional words elicit selective responding relative to neutral words, such as in lexical decision, naming, automatic response inhibition and vigilance tasks (Algom, Chajut, & Lev, 2004;Estes & Verges, 2008;Kanske & Kotz, 2007;Kousta, Vinson, & Vigliocco, 2009;Larser, Mercer & Balota, 2006;Pratto & John, 1991). This effect of emotional words cannot be simply reduced to an enhanced word concreteness effect.…”
Section: The Impact Of Emotional Semantic Content On Stmmentioning
confidence: 99%
“…Twelve words for each category were selected. Because length and average orthographic neighborhood (Footnote 3) tend to be related to word recognition speed (Larsen, Mercer, & Balota, 2006), we analyzed these important lexical characteristics. The words in these four categories did not differ neither in length, F (3, 9) = .49, p > .50, nor in orthographic neighborhood, F (3, 9) = .23, p > .50.…”
Section: Accessibility Of Aggression-and To Fear-related Semantic Conmentioning
confidence: 99%
“…Although an advantage for negative words has not been consistently reported, especially using tasks such as the Emotional Stroop task where negative words tend to lead to slower RTs (but see Larsen, Mercer, and Balota, 2006 for a review), a general difference in processing emotional vs. neutral words is well established.…”
mentioning
confidence: 99%